Tanjong life! - Mohd Azmi Mohd Hussin (Clarity Publishing, 2015)
Tanjong Life features the cheeky adventures of Joe G as he explores Penang's nooks and crannies; sampling the best food, visiting secret scenic spots, and experiencing all the fun that the island has to offer. With his big heart and friendly nature, true-blue Penangite Joe G is the perfect guide to the beautiful, truly incomparable 'Pearl of the Orient'.